Generalized Hartmann-Shack array of dielectric metalens sub-arrays for polarimetric beam profiling - Zhenyu Yang (Nature Portfolio, 2018)
Obtaining information on the amplitude, phase and polarization profile of optical beams is of huge interest. Here, the authors create a generalized Hartmann-Shack array with metalenses which measures phase and phase-gradient profiles of optical beams but also measures spatial polarization profiles at the same time.